OC-09 - Microparticle-mediated transfer of TF hypercoagulability between cancer cells. Issue 140 (April 2016) - Shaker, H.; Rothmeier, A.S.; Kirwan, C.C.; Ruf, W.
Abstract : Introduction: Tissue Factor (TF) promotes apoptosis-resistance and facilitates haematogenous metastasis. Cancer cells release TF-bearing microparticles (TF-MP) which have pro-coagulant activity. TF-MPs from cancer cells induce increase in TF expression and procoagulant activity of recipient endothelial cells. Drug resistance microparticles transfer between cancer cells, resulting in induction of recipient cell drug resistance, however transfer of TF-MPs between cancer cells has not been demonstrated. Aim: To determine if microparticles isolated from TF expressing cancer cell lines can induced TF-mediated procoagulant activity in cell lines that do not express TF. Materials and Methods: A7 cells (a melanoma cell line that does not express TF) were transformed to express TF with adenoviral transformation. In addition, the TF-expressing breast cancer cell line MDAMB231 was used. Media was collected from (1) wild-type A7 (A7-WT) cells, which acted as control (2) MDAMB231 cells, (3) A7 cells transformed with 'low' levels of TF-adenovirus and (4) A7 cells transformed with 'high' levels of TF-adenovirus. MPs were isolated from media by centrifugation using standard techniques. Isolated MPs were incubated with wild-type A7 (A7-WT) cells overnight. Pro-coagulant activity of A7-WT cells was assessed using a FXa generation assay. Results: i) A7-WT cells incubated overnight with MDAMB231-derived MPs produced an almost 5 fold increase in procoagulant activity compared to control (Mean 3.5 mOD/min S.E 0.32 vs control 0.68 S.E. 0.05, p < 0.01). ii) MPs released from A7-TF cells induced a dose-dependant increase in cell based procoagulant activity when incubated with A7-WTs compared to control:A7-WT cells incubated with control MPs (Control): mean mOD 0.83, S.E. 0.07A7-WT cells incubated with A7-TF derived MPs (low levels of TF-adenovirus): mean mOD 1.27, S.E. 0.06 (p = 0.04 vs control)A7-WT cells incubated with A7-TF derived MPs (low levels of TF-adenovirus): mean mOD 2.77, S.E. 0.23 (p < 0.01 vs control). Conclusions: These results demonstrate, for the first time, microparticle-mediated transfer of TF procoagulant activity between cancer cells. MPs shed by cancer cells in vivo have been implicated in cancer cell progression and hypercoagulability. The acquisition and spread of of MP-mediated TF activity has implications for cancer cell biology and cancer-induced hypercoagulability.